Microbiota in mesenteric adipose tissue from Crohn’s disease promote colitis in mice - Zhen He (BMC, 2021)
Abstract Background Mesenteric adipose tissue (mAT) hyperplasia, known as creeping fat is a pathologic characteristic of Crohn’s disease (CD). The reserve of creeping fat in surgery is associated with poor prognosis of CD patients, but the mechanism remains unknown. Methods Mesenteric microbiome, metabolome, and host transcriptome were characterized using a cohort of 48 patients with CD and 16 non-CD controls. Multidimensional data including 16S ribosomal RNA gene sequencing (16S rRNA), host RNA sequencing, and metabolome were integrated to reveal network interaction. Mesenteric resident bacteria were isolated from mAT and functionally investigated both in the dextran sulfate sodium (DSS) model and in the Il10 gene-deficient (Il10 −/−) mouse colitis model to validate their pro-inflammatory roles. Results Mesenteric microbiota contributed to aberrant metabolites production and transcripts in mATs from patients with CD. The presence of mAT resident microbiota was associated with the development of CD. Achromobacter pulmonis (A. pulmonis) isolated from CD mAT could translocate to mAT and exacerbate both DSS-induced and Il10 gene-deficient (Il10 −/−) spontaneous colitis in mice. The levels of A. pulmonis in both mAT and mucous layer from CD patients were higher compared to those from the non-CD group. Conclusions This study suggests that the mesenteric microbiota from patients with CD sculpt a detrimental microenvironment and promote intestinal inflammation. Video abstract